Drowning rates among children and adolescents (aged 7–17) in Israel during the years 2008–2018 - Sigalit Abihasira; Daniel S. Moran; Daniela Orr; Uri Eliyahu (BMC Public Health, 2023)
Abstract Objective Drowning is one of the leading causes of death among children and youth worldwide. This study aims to examine differences in the rates of drowning (fatal and non-fatal drowning) among children and youth in Israel stratified by age, sex, sector, place of drowning, and the drowning outcome. In addition, we compared the results of studies reported in other countries in specific age groups based on statistics of about 100,000 drowning cases. Method A statistical analysis of 474 drownings between 2008 and 2018 was conducted. All cases refer to youngsters aged 7–17 in the State of Israel. Statistical analysis was performed on data obtained from the Beterem – Safe Kids Israel organization and from the Israel Central Bureau of Statistics. Disparities between groups within the examined population were analyzed based on gender, sector (Jewish versus non-Jewish), and drowning site. Results Of the 474 drownings that occurred during 2008–2018, 38.4% ended in death. 79% of the cases occurred in pools. The Arab minority sector (21.1% of the general population) accounted for 25.1% of all drownings, males accounted for 70.5% of the drowning cases, and the age group with the most drownings (48.5%) was that of 15–17 years. The Jewish population was involved in more than 75% of drownings in places designated for bathing and in more than 83% of all disaster scenarios, whereas the Arab minority was involved in more than 61% of drownings in places not designated for bathing. Conclusions The results are comparable to those of other studies worldwide. Boys drown twice as much as girls, mainly in the age group of 15–17. This may be explained by overconfidence in boys and a tendency to overestimate their actual swimming abilities. Most drownings occur in pools. Drowning among the Jewish population occurs mainly in designated bathing sites. Practical applications The findings can and, in fact, must be used to inform and educate the younger generation as to the potential dangers involving bathing in designated bathing sites.